Analysis of Effectiveness of Change of Training Program with Adkar Approach (Awareness, Desire, Knowledge, Ability and Reinforcement) - Ainur Leksono; Praptini Yulianti (Jurnal Multidisiplin Madani, 2022)
Every organisation must experience changes to survive and develop amid increasingly fierce business competition, especially during the Covid-19 pandemic. This study identifies essential changes in the company using the ADKAR model (Awareness, Desire, Knowledge, Ability, Reinforcement) before and after the pandemic. It makes suggestions for improvements to increase the effectiveness of employee performance. The research object is a company engaged in training, namely the Edu Prima Cemerlang Training Institute Surabaya, using 5 (five) Key Informants. Data mining is carried out through in-depth interviews, and then the data obtained will be validated through FGD. The results of this study got strategic steps for neglecting ADKAR that can be applied, among others building awareness, among others, namely: (a) communication with directors and technicians; (b) preparation of materials following the time allocation; (c) addition of training assistants; (d) creation of animations or creative media to help participants understand the training; (e) cooperation with several vendors who have studios; etc. At the creating desire stage, the following steps are carried out: (a) communication with directors and technicians regarding training innovations; (b) preparation of materials following the time allocation; (c) addition of training assistants; (d) efficiency of agency spending; etc. The foresting ability and reinforcing change stages include: (a) self-study; (b) job immersing; (c) webinars and simulations; (d) FGD (Focus Group Discussion); etc. Meanwhile, reinforcing change includes: (a) assistance; (b) personal coaching; (c) buddy system; (d) negotiations with studio owners; (e) increase in working capital through provision for operating profit; (f) equipment loans through financing institutions or banks; etc.